2018
DOI: 10.3390/en11051285
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Ground Stress Field and Advanced Prediction of Gas Outburst Risks in the Non-Mining Area of Xinjing Mine, China

Abstract: Abstract:In order to predict in advance the coal and gas outburst risks in the No. 3 coal seam in the non-mining area of the Xinjing mine, the strata were divided into seven rock assemblage types based on the lithologic characteristics of strata in the research area, and eight geological profile models were constructed. The finite element methods were used to simulate the ground stress field of the No. 3 seam floor. Based on the log curve, the coal structural type of the No. 3 coal seam was identified, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…B-1 Coalbed, Zhengzhou, Western Henan, China, where there have been frequent coal and gas outburst disasters over the last 60 years [7]. According to the new structural-genetic classification system [38], the TDC samples belong to medium-rank and mylonitic structure coal and are characterized by low strength and strong gas adsorption/desorption [32].…”
Section: Preparation and Testing Of Natural Coal Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…B-1 Coalbed, Zhengzhou, Western Henan, China, where there have been frequent coal and gas outburst disasters over the last 60 years [7]. According to the new structural-genetic classification system [38], the TDC samples belong to medium-rank and mylonitic structure coal and are characterized by low strength and strong gas adsorption/desorption [32].…”
Section: Preparation and Testing Of Natural Coal Samplesmentioning
confidence: 99%
“…As a result, most simulation studies only reported qualitative rather than quantitative results [13,31]. Today, the understanding of coal and gas outburst mechanism remained poor, the predictions were inaccurate and coal and gas outburst accidents still account for a large proportion of accidents in coal mines [14,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation is also widely used to study the modern tectonic stress field. Some scholars have obtained the geostress field of the coal seam floor by building geological profile models and using the finite element simulation method [18], or have studied the stress field near faults by combining different inversion methods [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the initial geo-stress field of rock masses is the basis for calculating stresses and displacements after excavation is performed in an underground engineering project [11]. Consequently, it is of great practical significance to understand the distribution of the initial geo-stress field of rock masses [12,13]. Moreover, because of difficult downhole conditions and high costs [14], measured in situ stresses are usually insufficient, such that it is difficult to use the measured in situ stresses to express the macroscopic distribution of the initial geo-stress field of rock masses.…”
Section: Introductionmentioning
confidence: 99%